2020
DOI: 10.1515/nanoph-2020-0435
|View full text |Cite
|
Sign up to set email alerts
|

Perspective on using multiple orbital-angular-momentum beams for enhanced capacity in free-space optical communication links

Abstract: Structured light has gained much interest in increasing communications capacity through the simultaneous transmission of multiple orthogonal beams. This paper gives a perspective on the current state of the art and future challenges, especially with regards to the use of multiple orbital angular momentum modes for system performance enhancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 61 publications
0
24
0
3
Order By: Relevance
“…High dimensional encoding and high-capacity communication are attractive topics and structured light applied in related fields has been researched for few decades [20,105,189,190]. Various properties of structured light such as OAM evolution and spatial mode structure have been demonstrated that can be used to improve high-dimensional cryptography and secure communication [191][192][193].…”
Section: High-capacity Encoding and Communicationmentioning
confidence: 99%
“…High dimensional encoding and high-capacity communication are attractive topics and structured light applied in related fields has been researched for few decades [20,105,189,190]. Various properties of structured light such as OAM evolution and spatial mode structure have been demonstrated that can be used to improve high-dimensional cryptography and secure communication [191][192][193].…”
Section: High-capacity Encoding and Communicationmentioning
confidence: 99%
“…In light optics, self-similar solutions of this equation, such as Hermite–Gauss and Laguerre–Gauss modes, 26 are routinely used in applications to optical communication. 27 Other examples include Airy 28 , 29 and similar accelerating beams, 30 as well as non-diffracting solutions such as Bessel beams. 31 , 32 Superoscillating beams, 33 which contain lobes with dimensions that are much smaller than a diffraction-limited spot, have also been realized with electron beams.…”
Section: Generation Of Special Electron Beam Modesmentioning
confidence: 99%
“…The OAM in this kind of beam is induced by a helical phase front given by an azimuthal phase dependence of the form e i φ , where represents the OAM number and φ the azimuthal angle [1][2][3][4][5]. Over the past decade, there has been an enormous interest in using photons carrying OAM for quantum communication [6][7][8][9][10][11][12]. These structured beams of light allow for the encoding of multiple bits of information in a single photon [3][4][5].…”
mentioning
confidence: 99%